Structural Reversibility and Nickel Particle stability in Lanthanum Iron Nickel Perovskite‐Type Catalysts. Issue 11 (11th May 2017) - Steiger, Patrick; Delmelle, Renaud; Foppiano, Debora; Holzer, Lorenz; Heel, Andre; Nachtegaal, Maarten; Kröcher, Oliver; Ferri, Davide
Abstract: Perovskite‐type oxides have shown the ability to reversibly segregate precious metals from their structure. This reversible segregation behavior was explored for a commonly used catalyst metal, Ni, to prevent Ni sintering, which is observed on most catalyst support materials. Temperature‐programmed reduction, X‐ray diffraction, X‐ray absorption spectroscopy, electron microscopy, and catalytic activity tests were used to follow the extent of reversible Ni segregation. LaFe1− x Ni x O3± δ (0≤ x ≤0.2) was synthesized using a citrate‐based solution process. After reduction at 600 °C, metallic Ni particles were displayed on the perovskite surfaces, which were active towards the hydrogenation of CO2 . The overall Ni reducibility was proportional to the Ni content and increased from 35 % for x= 0.05 to 50 % for x= 0.2. Furthermore, Ni could be reincorporated reversibly into the perovskite lattice during reoxidation at 650 °C. This could be exploited for catalyst regeneration under conditions under which impregnated materials such as Ni/LaFeO3± δ and Ni/Al2 O3 suffer from sintering. Abstract : Redox stable Ni catalyst : The reversible segregation behavior of Ni from a LaFe1− x Ni x O3± δ host lattice results in redox stable nickel metal catalysts. Redox stability is observed in terms of catalyst activity towards the hydrogenation of CO2 and under conditions relevant for catalyst regeneration, under which common Ni/support‐type catalysts suffer strongly from particle sintering. This could be directly linked to Ni segregation. Prolonged catalyst lifetimes may be a beneficial consequence.